Attitude and behaviour of Dutch Otorhinolaryngologists to Evidence Based Medicine. - Maaike M Rademaker; Adriana L Smit; Marlous F Kortekaas; Peter Paul G van Benthem; Inge Stegeman (PLoS ONE)
Objective The objective of this study was to assess the attitude and behaviour of Dutch ENT surgeons and ENT residents towards Evidence Based Medicine. Introduction Evidence Based Medicine is the cornerstone of modern clinical care. It is considered of crucial importance for optimal patient care and health care quality. Practicing it requires positive attitude and behaviour. Little is known about the attitude and behaviour towards Evidence Based Medicine in otorhinolaryngology. Methods We performed a web-based questionnaire among 607 Dutch Ear- Nose & Throat surgeons of whom 106 residents (cross-sectional study). The questionnaire consisted of 3 parts; (1) personal characteristics, (2) questions regarding Evidence Based Medicine attitude (McColl questionnaire, scale 0-100%) and (3) questions regarding Evidence Based Medicine behaviour (barriers and information seeking behaviour). Data were collected between March 26th 2018 and June 1st 2018. Results The median score on the overall McColl questionnaire was 50 (IQR 35). The main barriers respondents experienced were time related. Limited time in the outpatient clinic was considered a more important barrier for residents to practice EBM compared to ENT surgeons. Respondents' gut feeling and their own preference were identified as the main contributing factors in clinical decision making. Conclusion In conclusion Dutch ENT surgeons have a moderate attitude on the McColl questionnaire. The main barriers to practice Evidence Based Medicine they experience are time related.